A framework for supporting postgraduate research writing: insights from students’ writing experiences - Jeyaraj, Joanna Joseph; Wei, Keong Too; Lasito, Eni Ermawati (Taylor and Francis, 2022)
At postgraduate level, success often depends on the ability to produce quality academic writing. To develop a framework to support postgraduate research writing, we explored the writing experiences of twenty-four postgraduate students from non-native English-speaking backgrounds. Semi-structured interviews were conducted with these participants, who were enrolled in two institutions that have international branch campuses in Malaysia. Data were then analysed using an inductive thematic analysis approach. It was found that students’ research experiences centre around three areas: academic writing; supervisory support; and institutional support services and tools. From these insights, we now propose a framework containing three dimensions and argue for pedagogically driven writing support; pedagogically informed supervisory support; and targeted and systematic peripheral support. As this framework is driven by the experiences and needs of postgraduate students, we believe it could lead to a more enriching learning experience and also greater student satisfaction.